Endovascular occlusion of uterine arteries in the treatment of symptomatic uterine leiomyoma - Abishev Bakhyt; Rakhimzhanova Raushan; Tazhibaeyv Dulat (National Scientific Medical Center, 2017)
Objective: assess the condition of the uterus and myomatous nodes after EMA in diﬀerent periods by ultrasound and MRI. Methods. EMA was performed in 632 patients with various forms of uterine fbroids. To achieve this goal, 120 observations with various forms of uterine fbroids were analyzed. Results. Reduction of myomatous nodes according to ultrasound and MRI in 1 month was - 18.4-17.3%, after 3 months - 40.7-42.9%, after 6 months it was - 60.4-61.8% and through 12 months - 72.5-74.7% (р˂0.05) respectively. Necrotic isolation of the node, expulsion of myomatous nodes and removal of the partially submucous node giving birth was observed in n-18 (15%) cases. In n-12 (10%) observations, after uterine artery embolization, laparoscopic myomectomy of the subserousmyomatous nodes was performed. Conclusion. our experience shows that EMA is highly eﬀective method for treating uterine fbroids, performed depending on various forms alone or in combination with operational accommodation.